Essays on Borys Tkachenko’s stylistics within the context of the Kharkiv linguistic studies of the 1920s and early 1930s - Черемська, Ольга Степанівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
The article contains overview of the 1920s and 1930s Kharkiv linguistic school’s works in the sphere of the language culture and analysis of B. Tkachenko’s linguistic style conception argued in work “Essay of the Ukrainian stylistics” consisting of five lectures which were published as brochures in Kharkiv in 1930. It has been characterized that the scientist’s main ideas about essence and nature of relations between the literary language and the individual and people’s spoken one. The group and functional division that contains three basic way of speaking, 1) The daily spoken language “obykhidna” – ordinary, everyday, “familiarna”, vulgar, 2) The literary and poetical language; 3) The scientific and technical language, has been underlined. Attention was concentrated on the basic concepts of stylistics in B. Tkachenko’s interpretation. The concept “literary language” has been interpreted as a product of cultural development, consciously organized work piece that has to serve all spheres of society’s cultural activity; its normativity, stability, obligatoriness for the respective state of every citizen have been stressed.